The Comparison Between Evaluative Stance of Donald Trump and Hillary Clinton Realized in the Campaign Speeches of the United States Presidential Election 2016 - Novi, Aris; Fitriati, Sri Wuli; Sutopo, Djoko (English Education Journal, 2019)
The aim of the study was to compare and explain the appraisal resource of Donald Trump and Hillary Clinton realized in the campaign speeches of the United States Presidential Election 2016. This study is discourse analysis conducted by employing appraisal framework (Martin and White, 2005). It is focused on analyzing the appraising items of engagement utilized by the speakers in their first and last speech. The results show that in both speeches Trump produced 704 appraising items, while Hillary discovered 300 appraising items. Besides, it was also discussed that the engagement used contains more disclaim, such utilization by Trump was a medium to deliver his political agendas. While the existence of contrary position in Hillary’s speeches indicated her effort to clarify, even counter-strike all issues she dealt with. The similarities of appraising items utilized by the speakers were relied on both speeches, in the first speech, all features of engagement were deployed in the same configuration, while in the last speech, it happened only on disclaim and proclaim. Meanwhile, the differences of appraising items used were found in entertain and attribute in the last speech. In relation to the pedagogical implication, the study suggests that the English teaching and learning that adopts appraisal resource contextualized in hortatory text is an appropriate technique, the students are engaged to experience the relevant English language skills effectively and be able to produce text properly.